2007
DOI: 10.1108/13522750710819748
|View full text |Cite
|
Sign up to set email alerts
|

Brand, organization identity and reputation: SMEs as expressive organizations

Abstract: PurposeThe purpose of this research is to identify non‐sector‐specific brand and reputation‐based factors that distinguish successful entrepreneurs and small to medium‐sized enterprises (SMEs) from their larger counterparts. These distinguishing factors provide the building blocks for a theoretical (resource‐based view) model for demonstrating the pivotal role of brand, organizational identity (OI), and reputation building for large enterprises and small businesses in knowledge economies.Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 56 publications
4
83
0
1
Order By: Relevance
“…Unlike extant studies either within corporate marketing in general that tend to focus on large multinational enterprises (Abimbola and Kocak, 2007) or in the nascent area of corporate heritage brands and identities in particular, which have focused so far on well-known business and non-business organisations and brands (e.g. Urde et al, 2007;Balmer, 2011aBalmer, , 2011bHudson, 2011), the current study is situated within the empirical context of the UK's oldest brewery, viz.…”
Section: Shepherd Neame: Context and Company Backgroundmentioning
confidence: 99%
“…Unlike extant studies either within corporate marketing in general that tend to focus on large multinational enterprises (Abimbola and Kocak, 2007) or in the nascent area of corporate heritage brands and identities in particular, which have focused so far on well-known business and non-business organisations and brands (e.g. Urde et al, 2007;Balmer, 2011aBalmer, , 2011bHudson, 2011), the current study is situated within the empirical context of the UK's oldest brewery, viz.…”
Section: Shepherd Neame: Context and Company Backgroundmentioning
confidence: 99%
“…The intensity of competition in many industries has compelled firms to seek for new sources of competitive advantage from their available resources (Abimbola & Kocak, 2007). The assertion by Porter (1995) is strengthened by Keller (1993), who also indicated that firms endeavour to gain a sustained competitive advantage so as to earn profits in both the short and long terms.…”
Section: Brand Equity and Competitivenessmentioning
confidence: 82%
“…Baldauf et al (2003) found that the various antecedents of brand equity together significantly predict the performance of firms, which is inconsistent with the findings in this study. One explanation for this could be due to the size of Private Universities compared to that of Public Universities; in the two groups, the approach and focus of brand building differs significantly (Abimbola & Kocak, 2007). Other factors for the difference other than the size of the firm can be attributed to time, resource constraints and marketing knowhow (Krake, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that focus on the role of brand identity in SME internationalisation identify a range of facilitating factors that influence the development of brand identity and serve to support expansion (Abimbola and Kocak, 2007;Hutchinson et al 2007;Horan, O'Dwyer, and, Tiernan 2011;Mitchell, Hutchinson, and, Quinn 2013;Spence and Essoussi 2010). External facilitating factors include formal networking and partnering in foreign markets, consultancy assistance, along with parent company advantage to provide additional financial and intellectual capital.…”
Section: Innovativeness Proactivity and Risk-takingmentioning
confidence: 99%